The influence of air gap size and winding position on the proximity losses in high frequency transformers - Roßmanith, Hans; et al. (PESC 2001, Vancouver, 2001)
The effects of winding position and size of air gaps on proximity losses in high frequency transformers were investigated. The proximity losses were calculated using the analytical calculation of two-dimensional magnetic field distribution. The analysis was made on the basis of a boundary value problem.
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.lselek.theinf